Understanding the Theoretical Foundations of Inquiry-Based Learning: Pivot For Productive Science Education in Africa - Clara Dumebi Moemeke; Joy Nkiruka Chukwunenye; Nasrudeen Ayinde Malik (Educational Considerations, 2025)
Inquiry-based learning (IBL) represents a dynamic pedagogical approach in science education, driven by a foundation of deep theoretical constructs. This paper meticulously examines the cornerstone theoretical underpinnings of IBL, centering on constructivism, situated cognition, and cognitive load theories. Constructivism, epitomized by Piaget's cognitive constructivism and Vygotsky's social constructivism, underscores learners' active role in constructing knowledge and the significance of social interactions in this process. Situated cognition theory accentuates the value of learning within authentic contexts and the transferability of acquired knowledge and skills. Cognitive load theory contributes insights into optimizing cognitive resources for effective learning experiences. However, the high level of student autonomy during IBL has raised critical questions about its suitability in African science classrooms citing its opposing philosophical standpoint. Understanding these perspectives engenders a rich tapestry for a robust science education landscape that encourage a culture of engagement, critical thinking and complex problem-solving proficiency in science classrooms in Africa. This paper underscores the paramount importance of these theoretical foundations, advocating for their continued research-driven application to invigorate and refine IBL within the realm of science education In Africa. Through this concerted effort, the potential to foster a dynamic, transformative, and enduring IBL in the science education landscape will emerge.
Keywords: Inquiry; Inquiry-Based Learning; Theoretical Foundations; Science Education